UPAYA PENINGKATAN MOTIVASI BELAJAR PKN SISWA KELAS IV SD NEGERI 011 PAGARAN TAPAH DARUSSALAM MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY - Misnawati ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
This research is motivated by the lack of motivation to learn civics fourth grade students of SD Negeri 006 Pagaran Tapah Darussalam. This study aims to determine whether the motivation to learn civics fourth grade students of SD Negeri 011 Pagaran Tapah Darussalam can be enhanced through the implementation of cooperative learning model Two Stay Two Stray, which is carried out for 1 month. Subjects in this study is the fourth grade students of SD Negeri 011 Pagaran Tapah Darussalam 2016-2017 school year the number of students as much as 6 students, consisting of 4 boys and 2 girls. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the analysis and discussion as presented in chapter IV can be concluded that the application of the method two only two guests can enhance students' motivation fourth grade on the subjects of citizenship education in primary schools Tapah 011 Pagaran Darussalam. It can be seen from changes in student motivation in cycle 1 and cycle 2. Students 'motivation in the first cycle is 15 with an average of 41.7 students' motivation in lower categories and an increase in cycle 2 to 31 with an average of motivation to learn 86.1 students in the very high category. Based on the performance indicators that this research is successful if it reaches 75% of all students